Penerapan pendekatan cinematherapy untuk meningkatkan perilaku prososial pada siswa Bosowa International School Makassar - Haeruddin Niva (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2016)
The objectives of the research are: (i) to know the prosocial behavioral level of the students in Bosowa International School Makassar before and after giving cinematography approach, and (ii) to know whether or not the approach is able to enhance the prosocial behavior of the students in Bosowa International School Makassar. The research is a quantitative research using experimental method. The research design used is quasi experimental design with non-equivalent control group design. The data collection technique applied is scale and FGD (Focus Group Discussion). The findings shows that (i) the prosocial behavioral level of the students was low in pretest while after giving treatment there were significant increase to the prosocial behavior in the experimental group, and (ii) the cinematography approach was able to increase the prosocial behavior of the Grade VIII students in Bosowa Internatinal School Makassar.